COMPARISON OF SHEAR STRENGTH CEMENTATION OF PREHEATED RESIN COMPOSITE AND RESIN CEMENT ON INDIRECT LITHIUM DISILICATE - Hafisza Syalsyabila Maghfira; Rahmat Hidayat; Rizki Amalina (Jurnal Medali, 2022)
Background: The success of fixed dentures is influenced by the cementation procedure. Resin cement is the most commonly used luting materials. In addition to resin cement, there are other types of luting materials, preheated resin composite. Preheating resin composite allow the material to have a low level of viscosity, therefore can be used as luting material. The purpose of this study was to evaluate the comparison of the shear strength cementation of preheated resin composite and resin cement on indirect lithium disilicate.Method: This study is experimental laboratory with post test only control group design. The sample in this study are 12 pieces lithium disilicate with diameter 5.5 mm x 3 mm cemented divided into three groups based on types of luting materials (preheated resin composite microhybrid, preheated nanohybrid, and resin cement). After the cementation procedure, the samples were immersed in artificial saliva at 37ºC for 24 hours. The shear strength test was carried out with a universal testing machine. Data analysis with using One Way ANOVA.Result: The results of the average shear strength of each group were 11.98 MPa for preheated microhybrid, 11.41 MPa for preheated nanohybrid, and 14.22 MPa for resin cement. The results of the One Way ANOVA test showed that there was a significant differences between groups (p value 0.000).Conclusion: There was a significant difference in shear strength between preheated microhybrid, preheated nanohybrid, and resin cement. The highest shear strength was the resin cement group.